2013
DOI: 10.1111/jsm.12009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between AMS 700™ CX and Coloplast™ Titan Inflatable Penile Prosthesis for Peyronie's Disease Treatment and Remodeling: Clinical Outcomes and Patient Satisfaction

Abstract: Introduction The implantation of inflatable penile prosthesis (IPP) with simultaneous manual penile remodeling allows for men to undergo a single procedure aimed at correcting both the penile deformity/curvature and erectile dysfunction (ED). Aim To evaluate the clinical outcomes and patient satisfaction in men with Peyronie's disease (PD) and ED who underwent AMS 700™ CX and the newer Coloplast™ Titan inflatable penile prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 14 publications
1
72
0
Order By: Relevance
“…Several articles [17,22,40–42] refer to the acceptance of a secondary implant when the first implant fails (Table ). Caire et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several articles [17,22,40–42] refer to the acceptance of a secondary implant when the first implant fails (Table ). Caire et al.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that in a large percentage of cases, the penis becomes functionally straight alone with the inflation of the cylinders of an inflatable three-piece prosthesis (IPP) (61~90%) 40-42. Defining the need for intraoperative straightening maneuvers has been studied.…”
Section: Treatment Utilizing Penile Prosthesesmentioning
confidence: 99%
“…There have been numerous studies published until now which evaluated each type of prosthesis independently as regards the satisfaction of the patient, the partner and the surgeon. Similarly, studies have been conducted to assess both types of prostheses independently in very specific scenarios such as to evaluate new developments and technical advances of each of the prostheses, or to compare their effectiveness in special clinical situations such as for concomitant DE and Peyronie's disease treatment 379101112…”
Section: Introductionmentioning
confidence: 99%